A study on the factors that influence financial wellbeing among employees in Petronas Dagangan Berhad / Azlandin Abdul Aziz and Nur Izyan Mohd Daud - Abdul Aziz, Azlandin; Mohd Daud, Nur Izyan (Faculty of Business and Management, 2015)
The purpose of this study is to identify the factors that influence the financial wellbeing among employees in PETRONAS Dagangan Berhad. This study will identify whether there is significance relationship between independent variables which are financial literacy, financial behavior and childhood experienced with financial wellbeing as the dependent variable.